Dengue in Taiwan: Pointing the finger at Aedes aegypti - Emma Louise Walton (Biomedical Journal, 2018)
In this issue of the Biomedical Journal we explore the history of dengue infection in Taiwan and what current trends have to say about the vector responsible for transmitting the disease on the island. We focus on original research reporting the development of a new perfusion bioreactor to engineer bone from human cord blood stem cells. Finally, we look at trends in osteoporosis in Taiwan and how they highlight the success of public health campaigns. Keywords: Dengue, Aedes aegypti, Mesenchymal stem cells, Osteogenic differentiation